Intraosseous neurofibroma versus schwannoma, importance of histological differential diagnosis in the definitive diagnosis: Case report (Research, Society and Development, 2021)
Neoplasms of neural origin represent 8% and 12% of all malignant and benign soft tissue neoplasms, respectively. In this group, tumors of the peripheral nerve sheath (TBNP) are inserted, a relatively rare group of diseases that are classified according to the specific characteristics of differentiation, cellular components and extracellular matrix. Neurofibroma and schwannoma are examples of lesions belonging to this group. The objective of this study is to present a clinical case of a female patient, 60 years old, diagnosed with a central lesion in the region of the right mandibular body. The lesion was discovered after a routine examination for prosthetic rehabilitation and, after incisional biopsy, initial diagnosis of schwannoma was obtained. The proposed treatment was a marginal resection, through the installation of a 2.4mm reconstruction plate and enucleation of the lesion. An escisional biopsy was then requested where neurofibroma was obtained as the final diagnosis. The patient had a satisfactory response to treatment, with no signs of recurrence. Although the decisive diagnosis of neurofibroma is based on histological findings, lesions such as schwannoma should be included as a differential histological diagnosis, which can hinder the definitive diagnosis. In this sense, peculiar characteristics of schwannoma and neurofibroma, their immunohistochemical behaviors and their similarities are necessary to trace their repercussions in establishing the diagnosis. Although there is no difference in treatment, such injuries may be associated which makes their final differentiation necessary, specifically for cases in which there is doubt.